(untitled) (Historia, 2022)
This issue of Historia has a fresh look with a new typeface and a stream-line referencing format: we hope that you approve of both. After the trialling of our new referencing system, our Author Guidelines have been tweaked for consistency –they are reproduced at the end of this issue as well as being available online. Thank you to our authors and copyeditor, Dr Bridget Theron, for working with us through these changes. As always, we are indebted to the peer reviewers whose valuable, voluntary, labours make it possible to continue publication through continued uncertain times of late pandemic, recession, unrest, and disaster in Southern Africa.